Analysis of problem solving processes based on released items of TIMSS-2011 (Edma 0-6: Educación Matemática en la Infancia, 2021)
This article analyzes the reasoning processes used by a sample of 111 students of fourth grade in solving a set of math questions that were part of the TIMSS 2011 study. Students have been asked to take special care on showing their reasoning and resolution processes. The assessment is checked according to the scoring guide and an inferential hypothesis test study is performed, in a second step, the resolution process is analyzed to explore students understanding, what and why they resolve the questions in such way. The main conclusions of the study are twofold: Firstly, the released items are shown to be a powerful tool to detect student learning problems. Secondly, identify factors that could explain the poor performance of student in problem solving resolution.
Keywords: TIMSS; Problem resolution (Problem solving); Learning errors